A high spatiotemporal study of somatic exocytosis with scanning electrochemical microscopy and nanoITIES electrodes. Issue 22 (24th May 2018) - Welle, Theresa M.; Alanis, Kristen; Colombo, Michelle L.; Sweedler, Jonathan V.; Shen, Mei
Abstract : Extra-synaptic exocytosis is an essential component of cellular communication. A knowledge gap exists in the exocytosis of the non-redox active transmitter acetylcholine. Using the nano-interface between two immiscible electrolyte solutions and scanning electrochemical microscopy, a high resolution spatiotemporal study of acetylcholine exocytosis is shown from individual neuronal soma. Abstract : Extra-synaptic exocytosis is an essential component of cellular communication. A knowledge gap exists in the exocytosis of the non-redox active transmitter acetylcholine. Using the nano-interface between two immiscible electrolyte solutions and scanning electrochemical microscopy (SECM), a high resolution spatiotemporal study of acetylcholine exocytosis is shown from an individual neuronal soma. The nanoelectrode was positioned ∼140 nm away from the release sites on the soma using an SECM. The quantitative study enables the obtaining of key information related to cellular communication, including extracellular concentration of the neurotransmitter, cellular permeability, Ca 2+ dependence on somatic release, vesicle density, number of molecules released and the release dynamics. Measurements were achieved with a high signal to noise ratio of 6–19. The released neurotransmitter with a concentration of 2.7 (±1.0) μM was detected at the nanoelectrodes with radii of 750 nm to 860 nm.